School-based educational innovations: case illustrations of context-sensitive evaluations. - Altschuld JW; Kumar DD; Smith DW; Goodway JD (Family & Community Health)
School-based educational innovations (new ideas and products) impact the quality of services offered individuals, families, and communities. Factors embedded in the context of a school often dictate whether innovations are adopted and implemented. To that end, the assessment of educational innovations should involve not only whether change occurred but also issues such as why change did or did not occur as a result of a program and its meaning to the participants. These issues can be addressed by expanding evaluation plans to include the context in which an innovation is embedded. In support of a context-sensitive evaluation model, the authors discuss three school-based health or physical education and science program assessment studies and an overall evaluation model. Methodological insights and implications for school and community-based studies are presented and include planning, conducting, recording, and interpreting context-sensitive evaluations. Copyright (c) 1999 by Aspen Publishers, Inc.